2016
DOI: 10.1080/13696998.2016.1199432
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of tuberous sclerosis complex in the UK: A retrospective cohort study in the Clinical Practice Research Datalink

Abstract: Background: Tuberous sclerosis complex (TSC) is a multi-system genetic disorder characterized by the development of diverse clinical manifestations. The complexity of this disease is likely to result in substantial challenges and costs in disease management throughout the patient's lifetime. This retrospective database study aims to quantify healthcare resources utilized by TSC patients. Methods: TSC patients in the Clinical Practice Research Datalink linked to the Hospital Episodes Statistics database were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 38 publications
8
33
3
Order By: Relevance
“…Exhaustive search of commercial and Medicaid databases in the United States indicates that TSC‐renal disease patients utilized more healthcare services than their matched controls, with an annual average total cost that is 10–20 times higher than that of control patients ( p < .05) (Song et al, ). Work from the United Kingdom confirms the high economic burden of TSC (Kingswood, Crawford, et al, ) and that renal complications are a major contributor to this cost (Kingswood, Nasuti, et al, ). The National Institute of Diabetes and Digestive and Kidney Diseases even convened a panel of experts working in the field to identify key unknowns and define possible “next steps” in advancing understanding of TSC‐dependent and mTORC1‐dependent renal disease (Henske, Rasooly, Siroky, & Bissler, ).…”
Section: Introductionmentioning
confidence: 89%
“…Exhaustive search of commercial and Medicaid databases in the United States indicates that TSC‐renal disease patients utilized more healthcare services than their matched controls, with an annual average total cost that is 10–20 times higher than that of control patients ( p < .05) (Song et al, ). Work from the United Kingdom confirms the high economic burden of TSC (Kingswood, Crawford, et al, ) and that renal complications are a major contributor to this cost (Kingswood, Nasuti, et al, ). The National Institute of Diabetes and Digestive and Kidney Diseases even convened a panel of experts working in the field to identify key unknowns and define possible “next steps” in advancing understanding of TSC‐dependent and mTORC1‐dependent renal disease (Henske, Rasooly, Siroky, & Bissler, ).…”
Section: Introductionmentioning
confidence: 89%
“…Vigabatrine is used significantly more often by children (43.2%) than adults (24.4%) as reported from UK data [23]. Several studies showed that individuals with TSC require between four and eight times more prescriptions than the general population [23,26,110]. In a UK study, hypnotics or antipsychotic drugs (not differentiated) were prescribed twice as often in individuals with TSC than in the general population.…”
Section: Health Care Resource Usementioning
confidence: 94%
“…In a UK study, hypnotics or antipsychotic drugs (not differentiated) were prescribed twice as often in individuals with TSC than in the general population. In particular, the difference was sevenfold in children with TSC as compared with in the general population [110]. However, in a French study in which 80% had intellectual disabilities and 70% had psychiatric disorders, only 20% received pharmacotherapy [53].…”
Section: Health Care Resource Usementioning
confidence: 95%
See 2 more Smart Citations